Arbitrase dan Media Sosial (Arbitration and Social Media) - Sanubari, Suar (UI Scholars Hub, 2024)
This article discusses the use of social media among arbitration actors. Social media have evolved since its inception. In the beginning, social networks were used to stay in touch with friends and family. Now the trend is to follow influencers. The boundaries between personal and professional use have become blurry. Social media are more regulated and supervised now, especially due to privacy and national security concerns. The social media adoption landscape has matured with increasing adoption by all generations. The use of social media can give rise to questions about ethical conduct or even the integrity of the arbitration proceedings. An arbitrator’s old post established evidence of bias; deleting old posts is tampering evidence; failing to use online resources such as social media can constitute professional incompetence or ineffective counsel. Regardless, social media also offers opportunities such as spreading awareness, networking, marketing, and improving the legitimacy of arbitration. The article describes the current state of the guidelines on social media use in arbitration and suggests its best practice.